The Application of Ant Colony Algorithm on Automatic Testing Path Optimization in Complex Circuits - Liu Xinmei; Liu Peng; Yin Junling; Hou Wen (2012 Third Global Congress on Intelligent Systems, 2012)
With the maturation of a large number of bionic optimization algorithm, based on the analysis of the currently common path optimization algorithm, ant colony optimization algorithm is applied to the problem of path optimization of automatic testing in complex circuit. This paper established the relevant system models, designed the specific implementation scheme, and conducted the simulation and experiment of path optimization on moving probe tests in small circuits and complex circuits. The results show that the ant colony algorithm applied to path optimization is feasible and it is superior to the results of sequence testing on the testing speed and real-time testing ability.